2019
DOI: 10.3389/fped.2019.00497
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis in Esophageal Atresia

Abstract: Recent studies have reported a higher prevalence of eosinophilic esophagitis in children with esophageal atresia. Under recognition of eosinophilic esophagitis in these patients may lead to excessive use of antireflux therapy and an escalation of interventions, including fundoplication, as symptoms may be attributed to gastroesophageal reflux disease. In addition, long-term untreated eosinophilic esophagitis may lead to recurrent strictures due to transmural esophageal inflammation, necessitating repeated dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…When a diagnosis of EoE is made in preschool-age children with EA, the most representative symptoms of the disease in the EA-EoE cohort seem to be vomiting and food intolerance [ 23 ], while older children from the general population with only EoE manifest the usual symptoms of EoE, such as dysphagia, food impaction and chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…When a diagnosis of EoE is made in preschool-age children with EA, the most representative symptoms of the disease in the EA-EoE cohort seem to be vomiting and food intolerance [ 23 ], while older children from the general population with only EoE manifest the usual symptoms of EoE, such as dysphagia, food impaction and chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…In EA patients, EoE is reported as 17% [ 4 , 7 ] and attributed to a possible genetic association and barrier defect in the esophageal mucosa caused by acid reflux or prolonged exposure to PPI therapy [ 3 ]. In this cohort of patients, symptoms of EoE are often misdiagnosed as GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who presented allergic symptoms or EoE symptoms underwent full allergic skin tests. The diagnosis of EoE was made according to the updated criteria of the AGREE Conference [ 7 , 14 ]. We diagnosed EoE in patients who had clinical symptoms and presented esophageal samples with >15 eosinophils/High Power Field (HPF), in the absence of other possible causes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of evidence showed that children with esophageal atresia (EA) (30-32) or with diaphragmatic hernia (34) are at higher risk to develop EoE (33, 34, 79). Several risk factors have been associated with the development of EoE in children with EA, such as early life factors, early exposure to acid suppressants and antibiotics, GERD, esophageal dysmotility, and epithelial injury (79). Interestingly, Krishnan et al demonstrated that children with EoE + EA share the same dysregulated genes (that encode for proteins involved in epithelial barrier functions and Th2 inflammation) compared to patients with EoE and without EA (33).…”
Section: Diseases Of Modern Life and Phenotypes Of Eoementioning
confidence: 99%